2015
DOI: 10.4254/wjh.v7.i8.1012
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptors as targets to treat non-alcoholic fatty liver disease

Abstract: and microsomal omega-oxidation, being markedly decreased by high-fat (HF) intake. PPAR-beta/delta is crucial to the regulation of forkhead box-containing protein O subfamily-1 expression and, hence, the modulation of enzymes that trigger hepatic gluconeogenesis. In addition, PPAR-beta/delta can activate hepatic stellate cells aiming to the hepatic recovery from chronic insult. On the contrary, PPAR-gamma upregulation by HF diets maximizes NAFLD through the induction of lipogenic factors, which are implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 84 publications
(86 reference statements)
4
104
0
2
Order By: Relevance
“…7). By having opposite functions, Pparα and Pparγ regulate fat metabolism and while Pparγ promotes lipid storage and Pparα promotes lipid utilization (Ables 2012, Kawano & Cohen 2013, Souza-Mello 2015. In the present study, prenatal hyperandrogenization decreased Pparα levels in the liver of PHanov animals, suggesting that this group could be more sensitive to hepatic steatosis.…”
Section: Discussionsupporting
confidence: 48%
“…7). By having opposite functions, Pparα and Pparγ regulate fat metabolism and while Pparγ promotes lipid storage and Pparα promotes lipid utilization (Ables 2012, Kawano & Cohen 2013, Souza-Mello 2015. In the present study, prenatal hyperandrogenization decreased Pparα levels in the liver of PHanov animals, suggesting that this group could be more sensitive to hepatic steatosis.…”
Section: Discussionsupporting
confidence: 48%
“…Taken together, these findings suggest that the identified miRNA-targeted genes contribute to regulating genes and pathways that are involved in adipogenesis, which may help to define the fat deposition differences between two groups of pigs. Recently, it has been shown that targeting PPARs is a potential way to treat NAFLDs [63,64]. Since the miRNAs that we uncovered in our study regulate the PPAR pathway, this study helps us understand the players involved in the regulation of this pathway and could provide insights into better treatment for NAFLDs.…”
Section: Discussionmentioning
confidence: 92%
“…In both alcohol-and methionine-choline-deficient models of hepatic lipid accumulation, elimination of PPARa signaling increases the resulting hepatic lipid accumulation (Ip et al 2003. Accordingly, PPARa agonist treatment in fatty liver models consistently decreases hepatic steatosis (Ide et al 2004, Larter et al 2012, Barbosa-da-Silva et al 2015, Souza-Mello 2015.…”
Section: Hepatic Lipids As Signaling Moleculesmentioning
confidence: 99%